On the mechanical behaviour of PEEK and HA cranial implants under impact loading - Garcia-Gonzalez, D; Jayaratnam, J; Sotiropoulos, S; Yoon, S; Cook, J; Siviour, C; Arias, A; Jerusalem, A (Elsevier, 2017)
The human head can be subjected to numerous impact loadings such as those produced by a fall or during sport activities. These accidents can result in skull fracture and in some complex cases, part of the skull may need to be replaced by a biomedical implant. Even when the skull is not damaged, such accidents can result in brain swelling treated by decompressive craniectomy. Usually, after recovery, the part of the skull that has been removed is replaced by a prosthesis. In such situations, a numerical tool able to analyse the choice of prosthesis material depending on the patient's specific activity has the potential to be extremely useful for clinicians. The work proposed here focuses on the development and use of a numerical model for the analysis of cranial implants under impact conditions. In particular, two main biomaterials commonly employed for this kind of prosthesis are polyether-ether-ketone (PEEK) and macroporous hydroxyapatite (HA). In order to study the suitability of these implants, a finite element head model comprising scalp, skull, cerebral falx, cerebrospinal fluid and brain tissues, with a cranial implant replacing part of the skull has been developed from magnetic resonance imaging data. The human tissues and these two biocompatible materials have been independently studied and constitutive models for both are provided here. A numerical model of the human head under impact loading is then implemented and validated, and a numerical comparison of the mechanical impact response of PEEK and HA implants is presented. This comparison was carried out in terms of the effectiveness of both implants in ensuring structural integrity and preventing traumatic brain injury. The results obtained in this work highlight the need to take into account environmental mechanical considerations to select the optimal implant depending on the specific patient: whereas HA implants present attractive biointegration properties, PEEK implant can potentially be a much more appropriate choice in a demanding mechanical life style. Finally, a novel methodology is proposed to assess the need for further clinical evaluation in case of impact for both implants over a large range of impact conditions.